CHILDREN WITH SPECIAL EDUCATIONAL NEEDS ACCOMODATED IN FOSTER FAMILIES IN REPUBLIC OF MACEDONIA (Annual of the Faculty of Philosophy in Skopje, 2011)
With the Social Protection Law, Republic of Macedonia provides help for the children without parents and parental care, on a population-wide basis or only for the children with special educational needs, through one of the forms of non-institutional protection, fostering in an another family. Placing children in fosters families provides existence and progress in the family environment, surrounds them with love, happiness and understanding. This form of protection is being developed for decades in the Republic of Macedonia but with the beginning of the process of deinstitutionalization it becomes particularly positive amongst this children 's category. 70 families in Macedonia in six cities are fostering special educational needs children, with a total of 107 children being placed there.
Keywords: CHILDREN WITH SPECIAL EDUCATIONAL NEEDS; FOSTER FAMILIES; NON-INSTITUTIONAL PROTECTION; DEINSTITUTIONALIZATION